2014
DOI: 10.1159/000356771
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Factors Related to Mortality and Survival: A Mini-Review

Abstract: As the world's population ages, elderly people are becoming an increasingly important group that merits special attention with regard to health and social issues. Lifestyles affect health and survival at all ages, but the consequences of poor lifestyle behaviors may be different for elderly people than for younger adults. They can also be heavily dependent on exposure earlier in life. Our current state of knowledge is based predominantly on studies conducted among middle-aged adults or young elderly people. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(90 citation statements)
references
References 39 publications
6
80
0
4
Order By: Relevance
“…The health of the elderly proceeds on a continuum that begins with development symptoms associated with daily activity changes, musculoskeletal degenerative, cognitive impairment, continues to disease onset, functional loss and disability, and ultimately, terminal status and death. [6][7][8] The regular physical activity (PA) can improve PF and health as prevention disease problem. [9][10][11] Several studies have shown that physically active adults are healthier and have a higher PF than inactive adults throughout different nations and populations groups.…”
Section: National Journal Of Physiology Pharmacy and Pharmacologymentioning
confidence: 99%
“…The health of the elderly proceeds on a continuum that begins with development symptoms associated with daily activity changes, musculoskeletal degenerative, cognitive impairment, continues to disease onset, functional loss and disability, and ultimately, terminal status and death. [6][7][8] The regular physical activity (PA) can improve PF and health as prevention disease problem. [9][10][11] Several studies have shown that physically active adults are healthier and have a higher PF than inactive adults throughout different nations and populations groups.…”
Section: National Journal Of Physiology Pharmacy and Pharmacologymentioning
confidence: 99%
“…Therefore, we have eventually selected also mathematical models, statistical studies and simulation approaches on obesity involving dynamical systems, network analysis or agent-based modeling. [20]). Bottom: the Overview, Design concepts and Details (ODD) protocol (from [21]).…”
Section: A Systematic Reviewmentioning
confidence: 99%
“…The diagram in Figure 4 (top) classes the factors of obesity into three categories [20]: the first describes environmental determinants, including social and physical factors; the second includes psychological and behavioral factors; and the third consists of biological factors [22], notably the genetic background of the concerned individual [23][24][25][26][27]. A summary diagram ( Figure 5) is carried out on the basis of [20] to illustrate the successive stages of the extraction of 106 studies selecting many factors on three important levels, namely: (i) environmental; (ii) psychological and behavioral; and (iii) biological. Among all of the tools from systems science used in public health, the network-based models are well suited to account for the collective behavior in the spread of obesity.…”
Section: A Systematic Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Each year, smoking leads about 5 million people to their end [3]. The hazards of smoking are related mostly to manifold increased risks of cancer development of different king including lung [4], kidney [5], larynx [6], bladder [7], stomach cancer [8] and some others.…”
Section: Introductionmentioning
confidence: 99%